Advancing Accounting Education: A Comprehensive Approach to Inventory Materials Learning through Online Applications and the Smith-Ragan Model - Alifia Ganeshi Anggarini; Elly Astuti; Elana Era Yusdita; Titik Ulfatun; Rosemarie J. Pascua; Ully Yunita Nafizah (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
Information technology has significantly influenced accounting and financial practices. This development was marked by several changes in the manual processing of accounting data into a computer accounting system with accounting software. While accurate online teaching materials exist, people still need to explain the logic behind using all the existing features and the related basic rules. This suggests that computer learning resources based on Accurate Educational accounting that discuss inventory could be developed further. This research aims to develop computer accounting teaching materials assisted by accurate online applications in an integrated manner with lesson plans, media, student worksheets, and assessment instruments. This research introduces an accurate online inventory-based inventory module, named Accurate Online, to help students to learn accounting computer material easier based on a scientific approach and problem-based learning. This research uses the Smith-Ragan model to test student responses to learning innovations and analyze their learning outcomes. The subjects in this study were 19 semester six students of the Accounting Education Study Program at PGRI Madiun University. This research develops learning innovations through lesson plans, modules, Student Worksheets, learning media, and evaluation instruments. The analysis results of the computer learning innovation process get very valid criteria with 95.42%, Lesson Plan 96.4%, worksheets 96%, learning media 92.5 %, and 96.25% evaluation instrument. Student responses to computer learning innovations for inventory module accounting based on Accurate Online get a practicality percentage of 87% in the practicality category, which is very practical and can be used without revision. Student learning outcomes have increased after participating in the Accurate Online-based accounting computer learning program. The value of the evaluation questions indicates the increase in student learning outcomes after learning is carried out using a structured learning program where 89% of students score above the Minimum Completeness Criteria.